The Online Evaluation of Courses: Impact on Participation Rates and Evaluation Scores - Groen, Jovan F; Herry, Yves (Canadian Journal of Higher Education, 2017)
At one of Ontario’s largest universities, the University of Ottawa, course evaluations involve about 6,000 course sections and over 43,000 students every year. This paper-based format requires over 1,000,000 sheets of paper, 20,000 envelopes, and the support of dozens of administrative staff members. To examine the impact of a shift to an online system for the evaluation of courses, the following study sought to compare participation rates and evaluation scores of an online and paper-based course evaluation system. Results from a pilot group of 10,417 students registered in 318 courses suggest an average decrease in participation rate of 12–15% when using an online system. No significant differences in evaluation scores were observed. Instructors and students alike shared positive reviews about the online system; however, they suggested that an in-class period be maintained for the electronic completion of course evaluations.